Effectiveness of Service-Learning - Peter Slepcevic-Zach; Karina Fernandez (Forum Neue Medien in der Lehre Austria, 2021)
The benefits of service-learning are explicitly mentioned in plenty development plans of different Austrian universities. To proof those benefits, effects of service-learning courses are often measured at the end of a specific course. Studies measuring effects a few years after completion of the course are rather rare. In this paper results of a study are presented, that focus on long-term effects. After a literature review focusing on service-learning as an instructional intervention as well as on the effectiveness of different Service-Learning courses, the implementation of the service-learning course discussed in this paper is described. 82 students, who had participated in service-learning-courses at the University of Graz, were interviewed three years after completing the course by means of a questionnaire. The results indicate the impact the service-learning-course had on the students in a long term run. The paper ends with the limitations of the presented research and the resulting outlook on further research.